2021
DOI: 10.3390/agronomy11081624
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Bell Pepper (Capsicum annuum L.) Plants with Application of Roholtiella sp. (Nostocales) under Soilless Cultivation

Abstract: Cyanobacteria are found to be renewable and sustainable additives for growth improvement in crops. Extracts and biomass of three nitrogen-fixing cyanobacteria namely, Roholtiella sp. (QUCCCM97), Nostoc ellipsosporum (QUCCCM99), and Desmonostoc danxiaense (QUCCCM112) isolated from Qatar desert environment were tested for their ability to enhance the growth of bell pepper (Capsicum annuum L.) seedlings. Soilless cultivation experiments were carried out by applying the biomass and the aqueous extract of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…extract in part per million (ppm) contained a considerable amount of Sodium (Na + ) 2.379, Ammonium (NH 4 + ) 0.674, Potassium (K + ) 8.533, Calcium (Ca 2+ ) 1.777, Magnesium (Mg 2+ ) 3.483, Fluoride (F − ) 0.0191, Chloride (Cl − ) 3.168, Nitrate (NO 3 − ) 5.247, Phosphate (PO 4 3− ) 13.67, Sulphate (SO 4 2− ) 0.212. In a like manner, the spectra scan of this strain showed that it contains a reasonable amount of phycoerythrin and phycocyanin [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…extract in part per million (ppm) contained a considerable amount of Sodium (Na + ) 2.379, Ammonium (NH 4 + ) 0.674, Potassium (K + ) 8.533, Calcium (Ca 2+ ) 1.777, Magnesium (Mg 2+ ) 3.483, Fluoride (F − ) 0.0191, Chloride (Cl − ) 3.168, Nitrate (NO 3 − ) 5.247, Phosphate (PO 4 3− ) 13.67, Sulphate (SO 4 2− ) 0.212. In a like manner, the spectra scan of this strain showed that it contains a reasonable amount of phycoerythrin and phycocyanin [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, even at zero salinity level, there was an incremental in the chlorophyll content level because of the growth enhancer potential of the Rholtiella sp. extract [ 17 ]. Generally, the proline accumulation increases faster in stressed plants at different conditions when compared with other amino acids [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations